Determinants of Bank-Specific and Macroeconomic on Profitability of Regional Bank in Indonesia - Jitendra Prasad Upadhaya; Sanju Kumar Singh (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
Regional Bank Profitability is one of challenging issues in Indonesian banking sector. Banking sector is lack generating higher profit then banks will get default and the effect shows to economy sector of each country. The source of data obtained from annual report of regional development banks (BPD) website and financial reports. This research covers the data over the period 2015-2019. This study includes major BPD banks of Indonesia. The analysis technique used to analyze the data in this study is done by classic assumption test, the multiple regression analysis. GDP is negative and significant, but Inflation is negative but not significant affect to profitability. Similarly, Banks specific variables Bank Size, CAR and BOPO. Finding shows that Bank size, CAR and BOPO are negative and significant to bank profitability.